1973
DOI: 10.1002/art.1780160317
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Induced Degenerative Joint Lesions Following Partial Meniscectomy in the Rabbit

Abstract: Degenerative lesions characterized by osteochondrophyte spur formation and cartilage degeneration were induced by partial meniscectomy in the rabbit knee. Cartilage degenerative lesions included ulceration, fissure and cyst formation, and diminished concentration of matrix proteinpolysaccharide. Proliferation of chondrocytes represented efforts at repair. Osteophytes increased in size with time. Changes resembled certain components of degenerative joint disease. The partial meniscectorny animal may be useful i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
111
0
10

Year Published

1988
1988
2006
2006

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 212 publications
(125 citation statements)
references
References 14 publications
4
111
0
10
Order By: Relevance
“…Experimental OA was induced bilaterally in female New Zealand white rabbits (specific pathogen-free, 6-8 weeks old, 1.8-2.3 kg; Hazelton Laboratories, Denver, PA) through the technique of partial medial meniscectomy (n = lo), as previously described (27). Age-matched sham-arthrotomized (n = 10) and nonoperated normal animals (n = 10) were used as controls.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental OA was induced bilaterally in female New Zealand white rabbits (specific pathogen-free, 6-8 weeks old, 1.8-2.3 kg; Hazelton Laboratories, Denver, PA) through the technique of partial medial meniscectomy (n = lo), as previously described (27). Age-matched sham-arthrotomized (n = 10) and nonoperated normal animals (n = 10) were used as controls.…”
Section: Methodsmentioning
confidence: 99%
“…The right knees of all dogs and the left knees of those animals treated with oral corticosteroids were dissected and examined for gross morphologic changes, including the presence of osteophyte formation and articular cartilage surface lesions. The severity of osteophyte formation was graded by measuring the maximal width (mm) of the spur on each medial and lateral femoral condyle, as described by Moskowitz et al (20). Because osteophytes are less often present and usually much smaller on tibial plateaus, this area was not included in the study protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The area size of articular surface changes (mm2) was measured under a dissecting microscope (Stereozoom; Bausch & Lomb, Rochester, N Y ) by the method previously described (20).…”
Section: Methodsmentioning
confidence: 99%
“…A pathologic process involving a response by the menisci has also been demonstrated in a model of experimental OA [IS]. It has been shown that partial loss of the meniscus results in mechanical disorders which cause articular cartilage degeneration in both humans [21,23,25,43] and animals [2,13,20,27,28,30]. The clinical long-term data have shown that articular cartilage degeneration cannot be avoided even when partial meniscectomy is performed arthroscopically [6,32,34].…”
Section: Introductionmentioning
confidence: 99%